Development of Interactive E-Module on Oxidation-Reduction Concept - Rabiatul Adawiyah; Susilawati Susilawati; Lenny Anwar S (Jurnal Tadris Kimiya, 2021)
This research aims to develop an interactive e-module on redox concept. Research and Development (R&D) method was used in this study with a Plomp model. This model included three phases: preliminary, prototype or development, and assessment. Validation sheets and response questionnaires were used as research instruments. Six expert lecturers, consisting of three media and materials experts each, assessed the validity sheets. A small-scale test was carried out utilizing two approaches; a one-to-one test and a small group test. A one-to-one test was given to three students who had high, medium, and low abilities; while the small group test was conducted on three teachers and 30 students from three different schools, which are MAN 2 Pekanbaru, MAN 1 Pekanbaru, and SMA IT Al-fitiyah. The results showed that the interactive e-module was very valid and could be used in learning activities. This is indicated by the percentage of validation from material experts 89.27% and media experts 88.76%. In a small-scale trial for a one-on-one test, the teacher's response 95.83% with very practical criteria; and student response test 87.73% with interesting criteria.